Sustainable copper extraction from printed circuit boards through urban mining: Evaluating environmental impact assessment - Nur Layli, Wirman; Kousalya, Subramaniam; Punitha Malar, Ravi; Fatin Zafirah, Mansur; Noor Intan Shafinas, Muhammad (AIP Publishing, 2025)
The rapid advancement of electronic devices has a remarkable technological progress, but it has also resulted in a significant surge in electronic waste (e-waste) generation, becoming a pressing concern for global and local communities. It’s fortunate that electronic waste contains a high number of precious metals, making it a valuable resource for recovery. This study focuses on extracting copper from Printed Circuit Boards (PCBs) using an urban mining approach, with a specific emphasis on assessing its environmental impact through the Life Cycle Assessment (LCA) method. The primary objective is to achieve a high yield of copper extraction by manipulating variables during the experimentation phase. The experimental results revealed an optimal copper yield of 85%, achieved with a 3-hour reaction time and a current of 1.0 mA. Furthermore, the comprehensive environmental assessment demonstrated that green electrolysis used in the extraction process imposes significantly less impact compared to conventional mining practices across various environmental aspects, including Global Warming Potential (GWP), acidification, eutrophication, ozone depletion air, ecotoxicity, human health particulate air, human toxicity (cancer and non-cancer), and the consumption of fossil fuels and smog air. These findings highlight the importance of adopting environmentally friendly approaches, such as green electrolysis, to retrieve valuable resources like copper.